A nosocomial salmonellosis outbreak caused by blaOXA-48–carrying, extensively drug-resistant Salmonella enterica serovar Goldcoast in a hospital respiratory care ward in Taiwan. (June 2022) - Chen, Chih-Ming; Tang, Hui-Ling; Ke, Se-Chin; Lin, Yi-Pei; Lu, Min-Chi; Lai, Yi-Chyi; Chen, Bo-Han; Wang, You-Wun; Teng, Ru-Hsiou; Chiou, Chien-Shun
Highlights: A nosocomial salmonellosis outbreak caused by bla OXA-48 -carrying, extensively drug-resistant (XDR) Salmonella Goldcoast. The OXA-48–producing XDR strains are susceptible to ceftazidime/avibactam. The deficiency of an MFS protein could link to elevated MICs to β-lactams. ABSTRACT: Objectives: A nosocomial salmonellosis outbreak caused by Salmonella enterica serovar Goldcoast occurred in a respiratory care ward (RCW) of a hospital in central Taiwan between December 24, 2020, and January 21, 2021. Ten isolates recovered from 10 RCW residents were resistant to extended-spectrum cephalosporins. The resistance mechanism needs to be investigated. Methods: Whole-genome sequencing and antimicrobial susceptibility testing were conducted to determine the genetic resistance determinants and the phenotypic resistance in the isolates. Results: Each of the 10 outbreak isolates harbored an IncHI2 plasmid that carried 15 antimicrobial resistance genes aac(3)-IId, aadA22, aph(3')-Ia, aph(6)-Id, arr-2, bla CTX-M-55, bla LAP-2, bla TEM-1, dfrA14, floR, lnu(F), qnrS13, sul2, sul3, tet(A), an efflux pump regulatory gene ramAp and an IncL plasmid carried a bla OXA-48 . The outbreak strains were expected to be resistant to numerous antimicrobials, including aminoglycosides, b-lactams /inhibitors, tetracycline, rifamycin, lincosamide, sulfonamides, trimethoprim, phenicols, fluoroquinolones, and carbapenems. Two outbreak isolates displayed higher minimum inhibitory concentrations than the other eight isolates to cefmetazole and carbapenems, which was linked to a deficiency of a major facilitator superfamily transporter in the two isolates. Conclusion: The carbapenem-resistant outbreak strains could have been derived from extensively drug-resistant S. enterica Goldcoast strains, which have been a major pathogen in Taiwan since 2018, through the acquisition of a bla OXA-48 -carrying plasmid. Special efforts are needed in Taiwan to monitor the spread of extremely resistant strains.